Autolysis of spent baker’s yeast generated from sago bioethanol fermentation: a preliminary study - Nik Nur Aziati, Mahmod; Nurashikin, Suhaili; Dayang Salwani, Awang Adeni; Awang Ahmad Sallehin, Awang Husaini; Siti Efliza, Ashari (World Researchers Associations, Indore, 2022)
Spent Baker’s yeast (Saccharomyces cerevisiae) is obtained as a by-product of ethanol fermentation industry and is mainly discarded as waste. The spent yeast can be potentially converted to yeast extract through autolysis process in which the yeast cells are lysed under certain conditions to release valuable and bioactive substances. To date, there are still limited studies on the autolysis of spent S. cerevisiae generated following the production of sago bioethanol. This research aims to investigate the feasibility of autolysis of spent Baker’s yeast generated from sago bioethanol fermentation by focusing on two important parameters namely initial pH and incubation time. The spent Baker’s yeast was autolysed at different initial pH values (3, 5 and 7) and at different incubation times (24, 48, 72 and 96 h). The protein and carbohydrate concentrations of the resulting lysates were analysed using Lowry assay and phenol-sulphuric acid assay respectively. Additionally, the surface morphology of the autolysed yeast cells was observed using Scanning electron microscope. Our results showed that the autolysis conducted at the initial pH of 3 gave the highest concentration of protein and total carbohydrate released from the lysate which were 2.5-fold and 2-fold over that in the control samples respectively. Meanwhile, the optimal incubation time for the autolysis of spent Baker’s yeast for both maximum concentrations of protein and carbohydrate released was found to be 72 h whilst prolonging beyond that did not result in any significant change of both the protein and total carbohydrate concentration. The morphological analysis of the lysed yeast cells clearly showed a significance change of the surface morphology indicative of cell lysis throughout the incubation period. In conclusion, the present work gives significant insights into the feasibility of autolysis of spent Baker’s yeast generated from sago bioethanol fermentation. This will in turn serves as useful fundamental information for developing potential side process streams within an integrated sago biorefinery in the future.